Clinical utility of Cone Beam Computed Tomography to define treatment in cases of medium and high endodontic complexity. - Germán Buchheister; Patricio Meléndez; Alejandro Herrera; Kevin Lever (Universidad de Concepción., 2019)
The aim of this study was to evaluate the clinical utility of Cone Beam Computed Tomography (CBCT) in cases of medium and high endodontic complexity. The relevance of CBCT to define treatment was evaluated through the Wittenberg questionnaire and the variation in treatment plans after CBCT exam analysis. The sample (n=40) was chosen for convenience over a period of 4 months. It considered the current recommendations to request CBCT exams before performing root canal treatments. Data collection was carried out through a survey applied to the treating clinicians, after examining the information obtained by the CBCT system. Data were analyzed with the Stata version 13 software, and the Chi-square test was used for inferential analysis. A 95% confidence interval was considered. The most frequent dental groups corresponded to upper posterior and upper anterior teeth (47.5% and 30.0%); the cases were equally distributed according to complexity (50% and 50%). The main reason for requesting CBCT exams corresponded to complex anatomy and/or atypical canal system (37.5%). The use of CBCT increased confidence in the initial treatment chosen by clinicians in 50% of cases according to the Wittenberg questionnaire, and a 45% variation in treatment plans was observed. There was no statistical relationship between complexity and the variables studied. CBCT contributed greatly to the therapeutic management of cases regardless of their complexity.